Polymers, resin films and dry films
Patent Information
- Application Number
- JP2021170161
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-18
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-10-18
AI Technical Summary
【0009】 本発明のポリマーは、高透明性及び高耐光性を有し、保護フィルム付きのドライフィルム化が可能である。
Smart Images

Figure 0007632223000001 
Figure 0007632223000002 
Figure 0007632223000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer, a resin film, and a dry film. [Background technology]
[0002] Transparent epoxy resins have traditionally been used as sealing and protective materials and adhesives in various optical devices, such as light-emitting diodes (LEDs) and CMOS image sensors.
[0003] In recent years, optical devices such as LEDs have become increasingly powerful, and they are required to have higher transparency and light resistance than before in order to suppress gas generation, discoloration, etc. Examples of materials that have particularly high transparency and light resistance include epoxy-modified silicone resins (Patent Documents 1 and 2).
[0004] On the other hand, the structure of optical devices is also becoming more complex, and it is necessary to seal flatly without introducing voids on substrates having uneven parts such as LEDs and wiring. Therefore, there is a demand for resins that can be supplied in the form of a dry film. However, the epoxy-modified silicone resins described in Patent Documents 1 and 2 have the problem that it is difficult to make them into dry films with protective films. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-94168 A [Patent Document 2] JP 2020-90649 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a polymer which not only has high transparency and high light resistance, but also can be made into a dry film with a protective film. [Means for solving the problem]
[0007] As a result of repeated studies to achieve the above object, the present inventors have found that a polymer having a main chain composed of a silylphenylene skeleton, an epoxy group-containing isocyanuric acid skeleton, and a norbornene skeleton can solve the above problems, and have completed the present invention.
[0008] Accordingly, the present invention provides the following polymer, resin film, and dry film. 1. A polymer having a main chain containing a silylphenylene skeleton, an epoxy group-containing isocyanuric acid skeleton, and a norbornene skeleton and not containing a siloxane skeleton. 2. The polymer according to 1, having a weight average molecular weight of 3,000 to 100,000. 3. The polymer according to 1 or 2, containing a repeating unit represented by the following formula (A1) and a repeating unit represented by the following formula (A2). [Chemical formula] (In the formula, a and b are positive numbers satisfying 0 < a < 1, 0 < b < 1, and a + b = 1. X 1 is a divalent group represented by the following formula (X1). X 2 is a divalent group represented by the following formula (X2).) [Chemical formula] (In the formula, R 11 and R 12 are each independently a hydrogen atom or a methyl group. R 13 is a hydrocarbylene group having 1 to 8 carbon atoms, and an ester bond or an ether bond may be interposed between its carbon-carbon bonds. n 1 and n 2 are each independently an integer from 0 to 7. The dashed line is a bond.) [Chemical formula] (In the formula, R 21 and R 22Each is independently a saturated hydrocarbyl group having 1 to 20 carbon atoms which may contain a hydrogen atom or a heteroatom. m is an integer of 0 or 1 to 10. The dashed line represents a bond.) 4. A polymer of 3 where 0 < a ≤ 0.35 5. A resin film obtained from any of the polymers of 1 to 4 6. The resin film of 5 where the transmittance of light with a wavelength of 405 nm of a film having a thickness of 10 μm made of the polymer is 95% or more 7. A dry film with a protective film comprising a support film, the resin film of 5 on the support film, and a protective film on the resin film
Advantages of the Invention
[0009] The polymer of the present invention has high transparency and high light resistance, and can be formed into a dry film with a protective film
[0010] [Polymer] The polymer of the present invention is a polymer whose main chain contains a silylphenylene skeleton, an epoxy group-containing isocyanuric acid skeleton, and a norbornene skeleton, and does not contain a siloxane skeleton
[0011] Such a polymer preferably contains a repeating unit represented by the following formula (A1) (hereinafter also referred to as repeating unit A1) and a repeating unit represented by the following formula (A2) (hereinafter also referred to as repeating unit A2).
Chemical formula
[0012] In formulas (A1) and (A2), a and b are positive numbers satisfying 0 < a < 1, 0 < b < 1, and a + b = 1, but preferably a satisfies 0 < a ≤ 0.35. If a is within this range, the solubility in general-purpose organic solvents is excellent and handling becomes easy
[0013] In formula (A1), X 1 is a divalent group represented by the following formula (X1). [ka] (The dashed lines represent bonds.)
[0014] In formula (X1), R 11 and R 12 are each independently a hydrogen atom or a methyl group, and preferably a hydrogen atom.
[0015] In formula (X1), R 13 is a hydrocarbylene group having 1 to 8 carbon atoms, and may have an ester bond or ether bond between its carbon-carbon bonds, but it is preferable that no ester bond or ether bond is present between the carbon-carbon bonds. The hydrocarbylene group may be linear, branched, or cyclic, and specific examples thereof include alkanediyl groups such as a methylene group, an ethane-1,1-diyl group, an ethane-1,2-diyl group, a propane-1,2-diyl group, a propane-1,3-diyl group, a butane-1,2-diyl group, a butane-1,3-diyl group, and a butane-1,4-diyl group. Of these, R 13 As the alkyl group, a methylene group or an ethylene group is preferable, and a methylene group is more preferable.
[0016] In formula (X1), n 1 and n 2 are each independently 0 to 7, preferably 0, 1 or 2.
[0017] In formula (A2), X 2 is a divalent group represented by the following formula (X2). [ka] (The dashed lines represent bonds.)
[0018] In formula (X2), R 21 and R 22are each independently a saturated hydrocarbyl group having 1 to 20 carbon atoms which may contain a hydrogen atom or a heteroatom. The saturated hydrocarbyl group may be linear, branched, or cyclic, and specific examples thereof include alkyl groups having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, or an n-decyl group; and cyclic saturated hydrocarbyl groups having 3 to 20 carbon atoms, such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a norbornyl group, or an adamantyl group. The saturated hydrocarbyl group may contain a heteroatom, and specifically, some or all of the hydrogen atoms of the saturated hydrocarbyl group may be substituted with halogen atoms such as fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms, and a carbonyl group, an ether bond, a thioether bond, or the like may be present between the carbon atoms. 21 and R 22 is preferably a hydrogen atom or a methyl group.
[0019] In formula (X2), m is an integer of 0 to 10, and is preferably 0, 1 or 2.
[0020] The polymer of the present invention preferably has a weight average molecular weight (Mw) of 3,000 to 100,000, more preferably 5,000 to 50,000. If Mw is within the above range, a solid polymer with no tackiness and excellent flexibility can be obtained, and it can also be made into a dry film with a protective film. In the present invention, Mw is a value measured in terms of polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as an elution solvent.
[0021] The polymer of the present invention may be one in which the repeating units A1 and A2 are bonded randomly or alternately, and may contain a plurality of blocks of each unit.
[0022] [Polymer manufacturing method] The polymer can be produced by addition polymerization of a compound represented by the following formula (1), a compound represented by the following formula (2), and a compound represented by the following formula (3) in the presence of a metal catalyst. [ka]
[0023] [ka] (In the formula, R 11 ~R 13 , n 1 and n 2 is the same as above.)
[0024] [ka] (In the formula, R 21 , R 22 and m are the same as above.)
[0025] Examples of the metal catalyst include platinum group metals such as platinum (including platinum black), rhodium, and palladium; platinum chloride, chloroplatinic acid, and chloroplatinic acid salts such as H2PtCl4·xH2O, H2PtCl6·xH2O, NaHPtCl6·xH2O, KHPtCl6·xH2O, Na2PtCl6·xH2O, K2PtCl4·xH2O, PtCl4·xH2O, PtCl2, and Na2HPtCl4·xH2O (wherein x is preferably an integer of 0 to 6, and particularly preferably 0 or 6); alcohol-modified chloroplatinic acid (for example, those described in U.S. Pat. No. 3,220,972) ); complexes of chloroplatinic acid and olefins (for example, those described in U.S. Pat. Nos. 3,159,601, 3,159,662, and 3,775,452); platinum group metals such as platinum black and palladium supported on supports such as alumina, silica, and carbon; rhodium-olefin complexes; chlorotris(triphenylphosphine)rhodium (the so-called Wilkinson's catalyst); complexes of platinum chloride, chloroplatinic acid or chloroplatinate with vinyl group-containing siloxanes (particularly vinyl group-containing cyclic siloxanes), and the like can be used.
[0026] The amount of the catalyst used is a catalytic amount, and is usually preferably 0.001 to 0.1 mass% relative to the total of the compound represented by formula (1), the compound represented by formula (2), and the compound represented by formula (3) as platinum group metal. In the polymerization reaction, a solvent may be used as necessary. As the solvent, for example, a hydrocarbon solvent such as toluene or xylene is preferable. As the polymerization conditions, from the viewpoint of not deactivating the catalyst and being able to complete the polymerization in a short time, the polymerization temperature is, for example, 40 to 150°C, particularly 60 to 120°C. The polymerization time depends on the type and amount of the polymer, but is preferably completed within about 0.5 to 100 hours, particularly 0.5 to 30 hours, in order to prevent moisture from entering the polymerization system. After the polymerization reaction is completed in this manner, if a solvent is used, it can be distilled off to obtain the polymer.
[0027] The reaction method is not particularly limited, but it is preferable to first mix and heat the compound represented by formula (2) and the compound represented by formula (3), add a metal catalyst to the mixed solution, and then dropwise add the compound represented by formula (1) over 0.1 to 5 hours.
[0028] The raw material compounds are preferably blended so that the molar ratio of the hydrosilyl group of the compound represented by formula (1) to the total of the alkenyl groups of the compound represented by formula (2) and the compound represented by formula (3) is preferably 0.67 to 1.67, more preferably 0.83 to 1.25. The Mw of the polymer of the present invention can be controlled by using a monoallyl compound such as o-allylphenol, or a monohydrosilane or monohydrosiloxane such as triethylhydrosilane as a molecular weight regulator.
[0029] [Resin film] The polymer of the present invention is dissolved in a solvent to form a resin solution, which is applied to a substrate made of a base material such as silicon, glass, metals such as iron, copper, nickel, and aluminum, or glass, and then heated at a temperature condition in the range of 80 to 300°C to form a film, thereby providing a resin film. The application method may be a known method, such as a dip method, a spin coating method, or a roll coating method. The polymer concentration in the resin solution is preferably 10 to 70% by mass, more preferably 20 to 60% by mass. The amount of the resin solution applied can be appropriately selected depending on the purpose, but it is preferable to apply the resin solution so that the thickness of the obtained resin film is preferably 0.1 to 200 μm, more preferably 1 to 150 μm. In addition, the obtained resin film preferably has a high transparency of 95% or more at a film thickness of 10 μm, and does not cause problems such as oil bleeding even if the resin film is continuously exposed to light at high temperatures.
[0030] The solvent is not particularly limited as long as it is a soluble solvent, and examples of the solvent include ketones such as cyclohexanone, cyclopentanone, and methyl-2-n-pentyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether (PGME), ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; and esters such as propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, propylene glycol mono-tert-butyl ether acetate, and γ-butyrolactone. Particularly preferred are ethyl lactate, cyclohexanone, cyclopentanone, PGMEA, γ-butyrolactone, etc. These organic solvents may be used alone or in combination of two or more.
[0031] [Dry film] The dry film with a protective film of the present invention comprises a support film, the resin film on the support film, and a protective film on the resin film.
[0032] Since the resin film does not contain a solvent, there is no risk of air bubbles caused by the evaporation of the solvent remaining inside the resin film and between the resin film and the uneven substrate.
[0033] The thickness of the resin film is preferably 5 to 200 μm, more preferably 10 to 100 μm, from the viewpoints of flatness on an uneven substrate, step coverage, and substrate lamination spacing.
[0034] In addition, the viscosity and fluidity of the resin film are closely related, and the resin film can exhibit appropriate fluidity in an appropriate viscosity range, and can penetrate deep into narrow gaps and strengthen adhesion to the substrate by softening the resin. Therefore, from the viewpoint of fluidity, the viscosity of the resin film is preferably 10 to 5,000 Pa·s, more preferably 30 to 2,000 Pa·s, and even more preferably 50 to 300 Pa·s at 80 to 120°C. In the present invention, the viscosity is a value measured using a rotational viscometer.
[0035] When the dry film of the present invention is adhered to a substrate having irregularities, the resin film conforms to the irregularities and covers the substrate, achieving high flatness. In particular, the resin film is characterized by low viscoelasticity, so that a higher flatness can be achieved. Furthermore, when the resin film is adhered to the substrate in a vacuum environment, the occurrence of gaps can be more effectively prevented.
[0036] The dry film of the present invention can be produced by applying the resin solution onto a support film and drying it to form a resin film. As the dry film production device, a film coater for producing adhesive products in general can be used. Examples of the film coater include a comma coater, a comma reverse coater, a multi-coater, a die coater, a lip coater, a lip reverse coater, a direct gravure coater, an offset gravure coater, a three-bar bottom reverse coater, and a four-bar bottom reverse coater.
[0037] When the support film is unwound from the unwinding shaft of the film coater and passed through the coater head of the film coater, the resin solution is applied to the support film in a predetermined thickness, and then the support film is passed through a hot air circulating oven at a predetermined temperature and time, and dried on the support film to form a resin film, thereby producing a dry film. In addition, the dry film is passed through a laminating roll at a predetermined pressure together with a protective film unwound from another unwinding shaft of the film coater to bond the resin film on the support film and the protective film, and then the dry film with a protective film is wound up on the winding shaft of the film coater, thereby producing a dry film with a protective film. In this case, the temperature is preferably 25 to 150°C, the time is preferably 1 to 100 minutes, and the pressure is preferably 0.01 to 5 MPa.
[0038] The support film may be a single-layer film made of a single film, or a multi-layer film made of a plurality of laminated films. Examples of the material of the film include synthetic resin films such as polyethylene, polypropylene, polycarbonate, and polyethylene terephthalate. Among these, polyethylene terephthalate is preferred because it has appropriate flexibility, mechanical strength, and heat resistance. These films may be subjected to various treatments such as corona treatment and release agent coating. Commercially available products may be used, such as Therapeel WZ (RX), Therapeel BX8 (R) (all manufactured by Toray Film Processing Co., Ltd.), E7302, E7304 (all manufactured by Toyobo Co., Ltd.), Purex G31, Purex G71T1 (all manufactured by Teijin DuPont Films Co., Ltd.), PET38×1-A3, PET38×1-V8, and PET38×1-X08 (all manufactured by Nippa Corporation).
[0039] The protective film may be the same as the support film described above, but polyethylene terephthalate and polyethylene are preferred because they have appropriate flexibility. Commercially available products may be used, and examples of polyethylene terephthalate include those already exemplified, and examples of polyethylene include GF-8 (manufactured by Tamapoly Co., Ltd.) and PE film type 0 (manufactured by Nippa Co., Ltd.).
[0040] The thickness of each of the support film and the protective film is preferably 10 to 100 μm, and more preferably 25 to 50 μm, from the viewpoints of stability in dry film production and prevention of curling around the core.
[0041] The method for laminating the dry film of the present invention onto a flat or uneven substrate is not particularly limited, but examples thereof include a method in which a protective film attached to the dry film is peeled off, and a vacuum laminator (product name: TEAM-300) manufactured by Takatori Corporation is used to set the degree of vacuum in a vacuum chamber to 50 to 1,000 Pa, preferably 50 to 500 Pa, for example 100 Pa, and the resin film to which the support film is attached is adhered to the substrate all at once at 80 to 300°C, and the pressure is returned to normal pressure, after which the substrate is cooled to room temperature, removed from the vacuum laminator, and the support film is peeled off. EXAMPLES
[0042] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, Mw was measured by GPC using a TSKGEL Super HZM-H (manufactured by Tosoh Corporation) as a GPC column under analysis conditions of a flow rate of 0.6 mL / min, tetrahydrofuran as an elution solvent, and a column temperature of 40° C., with monodisperse polystyrene as the standard.
[0043] The compounds used in the synthesis of the polymer are shown below. [ka]
[0044] [ka]
[0045] [ka]
[0046] [Example 1] Synthesis of polymer P-1 In a 10L flask equipped with a stirrer, a thermometer, a nitrogen purge device and a reflux condenser, 92.8g (0.35 mol) of compound (S-4) and 105.3g (0.65 mol) of compound (S-3b) were added, followed by adding 2,000g of toluene and heating to 70°C. Then, 1.0g of a toluene solution of chloroplatinic acid (platinum concentration 0.5% by mass) was added, and 194.0g (1.00 mol) of compound (S-1) was added dropwise over 1 hour (total of hydrosilyl groups / total of carbon-carbon double bonds = 1 / 1 (molar ratio)). After the dropwise addition was completed, the mixture was heated to 100°C and aged for 2 hours, after which toluene was distilled off from the reaction solution under reduced pressure to obtain polymer P-1. Polymer P-1 was obtained by 1 H-NMR (Bruker) did not detect a peak at around 4.5 ppm, which indicates the presence of SiH groups, and FT-IR (Shimadzu Corporation) did not detect a peak at 2200 cm, which indicates the presence of SiH groups. -1 No peak was detected near this point, and the Mw was found to be 4,000 by GPC measurement, confirming that the polymer contained repeating units A1 and A2.
[0047] [Example 2] Synthesis of polymer P-2 In a 10L flask equipped with a stirrer, a thermometer, a nitrogen purge device and a reflux condenser, 53.0g (0.20 mol) of compound (S-4) and 96.8g (0.80 mol) of compound (S-3a) were added, followed by adding 2,000g of toluene and heating to 70°C. Then, 1.5g of a toluene solution of chloroplatinic acid (platinum concentration 0.5% by mass) was added, and 194.0g (1.00 mol) of compound (S-1) was added dropwise over 1 hour (total of hydrosilyl groups / total of carbon-carbon double bonds = 1 / 1 (molar ratio)). After the dropwise addition was completed, the mixture was heated to 100°C and aged for 8 hours, after which toluene was distilled off from the reaction solution under reduced pressure to obtain polymer P-2. Polymer P-2 was obtained by 1 H-NMR (Bruker) did not detect a peak at around 4.5 ppm, which indicates the presence of SiH groups, and FT-IR (Shimadzu Corporation) did not detect a peak at 2200 cm, which indicates the presence of SiH groups. -1 No peak was detected near this point, and the Mw was found to be 41,000 by GPC measurement, confirming that the polymer contained repeating units A1 and A2.
[0048] [Example 3] Synthesis of polymer P-3 In a 10L flask equipped with a stirrer, a thermometer, a nitrogen purge device and a reflux condenser, 13.3g (0.05 mol) of compound (S-4) and 115.0g (0.95 mol) of compound (S-3a) were added, followed by adding 2,000g of toluene and heating to 70°C. Then, 2.0g of a toluene solution of chloroplatinic acid (platinum concentration 0.5% by mass) was added, and 194.0g (1.00 mol) of compound (S-1) was added dropwise over 1 hour (total of hydrosilyl groups / total of carbon-carbon double bonds = 1 / 1 (molar ratio)). After the dropwise addition was completed, the mixture was heated to 100°C and aged for 20 hours, after which toluene was removed from the reaction solution by vacuum distillation to obtain polymer P-3. Polymer P-3 was obtained by the following procedure: 1 H-NMR (Bruker) did not detect a peak at around 4.5 ppm, which indicates the presence of SiH groups, and FT-IR (Shimadzu Corporation) did not detect a peak at 2200 cm, which indicates the presence of SiH groups. -1 No peak was detected near this point, and the Mw was found to be 83,000 by GPC measurement, confirming that the polymer contained repeating units A1 and A2.
[0049] [Comparative Example 1] Synthesis of Comparative Polymer CP-1 In a 10L flask equipped with a stirrer, a thermometer, a nitrogen purge device and a reflux condenser, 26.5g (0.10 mol) of compound (S-4) and 108.9g (0.90 mol) of compound (S-3a) were added, followed by adding 2,000g of toluene and heating to 70°C. Then, 1.0g of a chloroplatinic acid toluene solution (platinum concentration 0.5% by mass) was added, and 184.3g (0.95 mol) of compound (S-1) and 9.3g (0.05 mol) of compound (S-2b) were added dropwise over 1 hour (total of hydrosilyl groups / total of carbon-carbon double bonds = 1 / 1 (molar ratio)). After the dropwise addition was completed, the mixture was heated to 100°C and aged for 6 hours, after which toluene was distilled off under reduced pressure from the reaction solution to obtain a comparative polymer CP-1 (siloxane unit content 19.9% by mass). The Mw of the comparative polymer CP-1 was 15,000.
[0050] [Comparative Example 2] Synthesis of Comparative Polymer CP-2 In a 10L flask equipped with a stirrer, a thermometer, a nitrogen purge device and a reflux condenser, 238.5g (0.90 mol) of compound (S-4) and 16.2g (0.10 mol) of compound (S-3b) were added, followed by adding 2,000g of toluene and heating to 70°C. Then, 1.0g of a chloroplatinic acid toluene solution (platinum concentration 0.5% by mass) was added, and 184.3g (0.95 mol) of compound (S-1) and 79.3g (0.05 mol) of compound (S-2b) were added dropwise over 1 hour (total of hydrosilyl groups / total of carbon-carbon double bonds = 1 / 1 (molar ratio)). After the dropwise addition was completed, the mixture was heated to 100°C and aged for 6 hours, after which toluene was distilled off under reduced pressure from the reaction solution to obtain a comparative polymer CP-2 (siloxane unit content 15.3% by mass). The Mw of the comparative polymer CP-2 was 7,000.
[0051] [Comparative Example 3] Synthesis of Comparative Polymer CP-3 In a 10L flask equipped with a stirrer, a thermometer, a nitrogen purge device and a reflux condenser, 79.5g (0.30 mol) of compound (S-4) and 377.3g (0.70 mol) of compound (S-3c) were added, followed by adding 2,000g of toluene and heating to 70°C. Then, 1.0g of a chloroplatinic acid toluene solution (platinum concentration 0.5% by mass) was added, and 174.6g (0.90 mol) of compound (S-1) and 158.5g (0.10 mol) of compound (S-2b) were added dropwise over 1 hour (total of hydrosilyl groups / total of alkenyl groups = 1 / 1 (molar ratio)). After the dropwise addition was completed, the mixture was heated to 100°C and aged for 6 hours, after which toluene was distilled off under reduced pressure from the reaction solution to obtain a comparative polymer CP-3 (siloxane unit content 20.1% by mass). The Mw of the comparative polymer CP-3 was 83,000.
[0052] [Comparative Example 4] Synthesis of Comparative Polymer CP-4 In a 10L flask equipped with a stirrer, a thermometer, a nitrogen replacement device and a reflux condenser, 132.5g (0.50 mol) of compound (S-4) and 409.0g (0.50 mol) of compound (S-3d) were added, followed by adding 2,000g of toluene and heating to 70°C. Then, 1.0g of a chloroplatinic acid toluene solution (platinum concentration 0.5% by mass) was added, and 174.6g (0.90 mol) of compound (S-1) and 302.0g (0.10 mol) of compound (S-2a) were added dropwise over 1 hour (total of hydrosilyl groups / total of alkenyl groups = 1 / 1 (molar ratio)). After the dropwise addition was completed, the mixture was heated to 100°C and aged for 6 hours, and then toluene was distilled off from the reaction solution under reduced pressure to obtain a comparative polymer CP-4 (siloxane unit content 29.7% by mass). The Mw of the comparative polymer CP-4 was 103,000.
[0053] [Light transmission test] Polymers P-1 to P-3 and comparative polymers CP-1 to CP-4 were each dissolved in cyclopentanone to a concentration of 50% by mass to prepare a resin solution. Each resin solution was applied onto a glass substrate, heated at 100°C for 5 minutes and then at 190°C for 2 hours in a nitrogen atmosphere to prepare a resin film (thickness 10 μm). The transmittance of light with a wavelength of 400 nm was measured. The results are shown in Table 1.
[0054] [Table 1]
[0055] [Light resistance test] The condition of the sample surface was checked by irradiating a 400 nm, 1 W laser for 1,000 hours on a sample made of the coating on a glass wafer obtained by the above method in an oven at 100° C. Samples that showed oil bleeding were marked with an X, and those that showed no change from the initial state were marked with an O. The results are shown in Table 2.
[0056] [Table 2]
[0057] [Preparation of dry film with protective film] Using a die coater as a film coater and a polyethylene terephthalate film (thickness 38 μm) as a support film, polymers P-1 to P-3 and comparative polymers CP-1 to CP-4 were each dissolved in cyclopentanone to a concentration of 55 mass%, and each was applied onto the support film. Next, the film was dried by passing through a hot air circulating oven (length 4 m) set at 100°C for 5 minutes to form a resin film on the support film, and a dry film was obtained. A polyethylene film (thickness 50 μm) was laminated as a protective film from above the resin film at a pressure of 1 MPa with a laminating roll, and the resin film and the protective film were laminated together, and then the film was wound up on the winding shaft of the film coater to produce a dry film with a protective film. At this time, the thickness of each resin film was set to 100 μm. Each dry film with protective film removed from the winding shaft was checked, and those in which cracks had already occurred in the resin coating, those in which the resin coating had stuck to the protective film when the protective film was removed, causing the resin coating to peel off from the support film, and those in which cracks had occurred when the protective film was removed were deemed difficult to make into a dry film with protective film as they could not be attached to a substrate, etc., and were marked with an ×. Those in which no abnormalities had occurred were deemed possible to make into a good dry film with protective film, and were marked with an ○. The results are shown in Table 3.
[0058] [Table 3]
[0059] From the above results, according to the present invention, it is possible to synthesize and provide polymers such as polymers P-1 to P-3 whose main chains are composed of a silphenylene skeleton, an epoxy group-containing isocyanuric acid skeleton, and a norbornene skeleton. In addition, the resin film obtained from the polymer is a highly transparent film with high light resistance that does not cause oil bleeding, etc. Furthermore, by using the resin film, it is also possible to provide a dry film with a good protective film.
Claims
1. A polymer having a main chain including a silphenylene skeleton, an epoxy group-containing isocyanuric acid skeleton, and a norbornene skeleton, and not including a siloxane skeleton, The weight average molecular weight is 3,000 to 100,000, A polymer containing only a repeating unit represented by the following formula (A1) and a repeating unit represented by the following formula (A2): 【Chemistry 1】 (In the formula, a and b are positive numbers satisfying 0<a<1, 0<b<1, and a+b=1. X 1 is a divalent group represented by the following formula (X1). X 2 is a divalent group represented by the following formula (X2).) 【Chemistry 2】 (In the formula, R 11 and R 12 each independently represent a hydrogen atom or a methyl group. R 13 is a hydrocarbylene group having 1 to 8 carbon atoms, and an ester bond or an ether bond may be present between the carbon-carbon bonds. n 1 and n 2 are each independently an integer of 0 to 7. The dashed lines represent bonds. 【Chemistry 3】 (In the formula, R 21 and R 22 each independently represent a hydrogen atom or a saturated hydrocarbyl group having 1 to 20 carbon atoms which may contain a heteroatom. m represents 0 or an integer of 1 to 10. The dashed lines represent bonds.)
2. 2. The polymer according to claim 1, wherein a satisfies 0<a≦0.
35.
3. A resin film obtained from the polymer according to claim 1 or 2.
4. 4. The resin film according to claim 3, wherein a transmittance of light having a wavelength of 405 nm through a 10 μm-thick film made of said polymer is 95% or more.
5. A dry film with a protective film, comprising: a support film; the resin film according to claim 3 on said support film; and a protective film on said resin film.
Citation Information
Patent Citations
Photosensitive resin composition, photosensitive dry film, and pattern forming process
JP2019200344A
Photosensitive resin composition, photosensitive resin coat, photosensitive dry film, and black matrix
JP2020016879A
Polysiloxane skeleton polymer, photosensitive resin composition, pattern forming process, and process for fabrication of opto-semiconductor device
JP2020090649A
Siloxane polymer containing isocyanuric acid skeleton and polyether skeleton, photosensitive resin composition, pattern forming method, and fabrication method of opto-semiconductor element
JP2020094168A